2008
DOI: 10.1080/11250000701866075
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of seminal receptacle and sperm storage inArmadillidium granulatumBrandt (Isopoda: Oniscidea)

Abstract: The aim of this study was to evaluate the efficacy of sperm storage in the seminal receptacle in females of Armadillidium granulatum after the first mating and in the absence of further mating. Females of A. granulatum were bred in the laboratory, isolated from males, until they were sexually mature, and then they were allowed to mate. They were then isolated again from the males and observed to evaluate their reproductive behaviour until their natural death. Some females were sacrificed at various time interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In all the species belonging to the families Porcellionidae, Trachelipodidae, Armadillidiidae and Armadillidae, which include the most evolved species of Oniscidea (Schmalfuss 1989), the organization pattern of the female genital system is always similar to that known from literature (Besse 1976;Longo et al 1998;Suzuki & Ziegler 2005;Longo & Trovato 2008) and denominated in the present paper as 'common pattern'. A similar pattern has been found in many species belonging to other families, even phylogenetically distant, such as Ligia italica (Ligiidae), Siciloniscus tulliae (Trichoniscidae), Stenoniscus carinatus (Stenoniscidae), Platyarthrus aiasensis (Platyarthridae), Armadilloniscus ellipticus (Detonidae), Chaetophiloscia elongata and Philoscia affinis (Philosciidae), and Oniscus asellus (Oniscidae).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In all the species belonging to the families Porcellionidae, Trachelipodidae, Armadillidiidae and Armadillidae, which include the most evolved species of Oniscidea (Schmalfuss 1989), the organization pattern of the female genital system is always similar to that known from literature (Besse 1976;Longo et al 1998;Suzuki & Ziegler 2005;Longo & Trovato 2008) and denominated in the present paper as 'common pattern'. A similar pattern has been found in many species belonging to other families, even phylogenetically distant, such as Ligia italica (Ligiidae), Siciloniscus tulliae (Trichoniscidae), Stenoniscus carinatus (Stenoniscidae), Platyarthrus aiasensis (Platyarthridae), Armadilloniscus ellipticus (Detonidae), Chaetophiloscia elongata and Philoscia affinis (Philosciidae), and Oniscus asellus (Oniscidae).…”
Section: Discussionsupporting
confidence: 51%
“…Another hypothesis could be founded on the variability of the paternal investment of trophic resources finalized to support ovogenesis and eggs maturation; some our preliminary ultrastructural investigations carried out on the seminal receptacle of Halophiloscia couchii, Halophiloscia hirsuta and Stenophiloscia glarearum (Longo and Trovato, unpublished results) have shown that a portion of the sperm stored in the lumen is captured by the epithelial cells of the seminal receptacle and then drawn into tubular cavities, as has been observed in the seminal receptacle of Porcellio laevis (Longo et al 1998), Armadillidium vulgare (Suzuki & Ziegler 2005) and Armadillidium granulatum (Longo & Trovato 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The female genital system of the oniscidean isopods has been the object of numerous researches (Besse, ; De Luca et al, ; Legrand and Vandel, ; Longo and Trovato, ; Longo et al, ; Mazzei et al, ; Suzuki and Ziegler, ; Vandel, ; Warburg, ; Wägele ).…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of testes, eVerent ducts, spermiogenesis and spermatozoal morphology and ultrastructure is indispensable for the study of reproductive biology and is of value for reconstruction of phylogenetic relationships in many animal taxa (Purschke and Jördens 2007;Longo and Trovato 2008;Tavares-Bastos et al 2008;Tourmente et al 2008) and in particular for all amphibians taxa (Baker 1965;Wake 1968Wake , 1970Williams et al 1984;Zalisko et al 1984;Brizzi et al 1992;Lee and Jamieson 1993;Selmi et al 1997Selmi et al , 1999Jamieson 2003a, b, 2006).…”
Section: Introductionmentioning
confidence: 98%